2017
DOI: 10.15406/jmen.2017.04.00099
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum 25-Hydroxyvitamin D and Thyroid Hormones in Pregnant Women in Amman-Jordan

Abstract: Aim: The aim of this study is to investigate changes of vitamin D and thyroid hormones levels during pregnancy to maintain normal fetus development and growth.Method: Serum hydroxyl vitamin 25(OH)D and thyroid levels were measured in109 pregnant women referred to our laboratory from prenatal clinic during the period of May to October 2015.Blood samples were detected for 25 (OH) vitamins D, TSH, FT4 and FT3 by chemiluminescent (Tosoh A1A, Japan).Results: Pregnant women aged 19-45years (18.2 years age average) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Both vitamin D and thyroid hormone bind to steroid hormone receptors, which are identical to one another 20 . A study found no link between vitamin D, FT4, or FT3 during pregnancy, however there was a significant link between vitamin D and decreased TSH in pregnant women with appropriate vitamin D levels (greater than 30 ng/ml) 13 . Despite vitamin D shortage among these women, no link was established between 25hydroxy vitamin D and thyroid function in a pregnancy research 14 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both vitamin D and thyroid hormone bind to steroid hormone receptors, which are identical to one another 20 . A study found no link between vitamin D, FT4, or FT3 during pregnancy, however there was a significant link between vitamin D and decreased TSH in pregnant women with appropriate vitamin D levels (greater than 30 ng/ml) 13 . Despite vitamin D shortage among these women, no link was established between 25hydroxy vitamin D and thyroid function in a pregnancy research 14 .…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the TSH levels are not dependent on the vitamin D supplementation and when compared with age and BMI, the TSH levels are not statistically significant after the vitamin D supplementation and these findings are in line with the previous studies. 13,14 table 3. Due to its activity in the thyroid gland and even in patients with thyroid disorders and thyroid autoantibody, several types of research have shown that vitamin D has an effect on thyroid hormone.…”
Section: Discussionmentioning
confidence: 99%